1976
DOI: 10.1088/0029-5515/16/2/020
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on maximum densities in tokamak experiments

Abstract: higher by a factor of 2 than the critical current that would be predicted for a runaway dominated discharge (Eq.( 27), Ref. [1]).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
156
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 5 publications
11
156
0
Order By: Relevance
“…Moreover, it is indeed worth mentioning than in RFX a further decrease in the I/N parameter seems to be prevented more by operative limitations than by plasma behaviour, since at high density the loop voltage increases dramatically. In any case, no evidence of disruptions, as those associated with the density limit in tokamaks [19,20], was observed.…”
Section: Global Power Balancementioning
confidence: 69%
“…Moreover, it is indeed worth mentioning than in RFX a further decrease in the I/N parameter seems to be prevented more by operative limitations than by plasma behaviour, since at high density the loop voltage increases dramatically. In any case, no evidence of disruptions, as those associated with the density limit in tokamaks [19,20], was observed.…”
Section: Global Power Balancementioning
confidence: 69%
“…At constant pressure, the fusion reaction is maximized at an optimum temperature on the order of 10 keV so plasma pressure cannot be arbitrarily partitioned between density and temperature. Reactor design studies typically find that densities on the order of 10 20 /m 3 are required [1]. The density at the optimum temperature can be computed as follows [2], using the most common empirical scaling for the density limit [3] The design for ITER (international thermonuclear experimental reactor) was constrained by the need to operate at these high densities with prediction of the density limit one of its most critical needs [4].…”
Section: Motivationmentioning
confidence: 99%
“…1) [8][9][10][11][12] or a stellarator ( Fig. 2) [13][14][15][16][17][18][19][20][21][22][23][24][25]. The vessel walls have to protect the hot plasma from the atmo spheric environment and the magnetic field reduces the plasma load to the inside of the vessel walls, while the neutrons leave the plasma and impinge nearly uni formly distributed onto the vessel walls.…”
mentioning
confidence: 99%
“…Due to instabilities of the distribution of the cur rent in the plasma [30][31], such as by changes in the plasma position or of the electric resistance of the plasma, caused by an uncontrolled density increase [25,32], such as the influx of impurity atoms released from the vessel walls, tokamaks have the problem of plasma confinement instabilities and plasma disrup tions in times of |is to ms. During the disruption the hot plasma and the major part of the magnetic energy of the plasma are deposited onto the vessel walls result ing in intense pulses of particle fluxes and high power deposition densities and the plasma is extinguished [33][34][35]. During normal operation of tokamaks, it has also been found that the loads to the vessel walls may oscillate, due to instabilities in the central plasma, such as "saw teeth" and "fishbone" oscillations [36] or instabilities in the boundary plasma, such as MARFES (multifaceted asymmetric radiation from the plasma edge) [37,38], and different ELMs (edge localized modes), giving a very large power deposition [39].…”
mentioning
confidence: 99%